Sustainable regional growth and development in the creative knowledge economy: Gender perspective on regional development and innovation in the food industry in Skåne - Kicki Stridh; Christina Scholten (European Regional Science Association (ERSA), 2010)
Gender perspective on regional development and innovation in the food industry in Skåne Working with applied research on gender, innovation and the food process industry in Skåne, we can conclude that gender is a necessary category in develop both industry and enhance regional development (Pettersson 2002, Scholten 2003, Sundin et al 2008). This conclusion has become evident (Lindberg et al 2008, Nyberg 2009, Pettersson 2007) as working consultants and researchers together (Norbäck et al 2006, Swärdh and Stridh2006), using workshops, strategic focus discussions and interviews in development work in the innovation hub The Skåne Food Innovation Network. Skåne is divided into regions where research and industry is concentrated to the south-west, with some exceptions. There are semi-rural areas, where businesses are small and often of self-employment character. These businesses attract women, working in sectors as food, tourism and health. One important issue for them to solve is how to reach the market and how to develop their businesses further. There are long-established structural power systems which need to be handled (Berglund et al 2007, Forsberg 1997) both by the individual entrepreneur but also by the facilitator organisations, like the innovation hub. Our project is one by several national projects, funded by Vinnovas TIGER programme, aiming at applying gender perspectives to innovative clusters for enhanced development. Three projects work in this context with issues of regional development. Ours is conducted together with The Skåne Food Innovation Network. In this paper we will draw attention to and discuss regional development and innovation policy out of a gender perspective, giving examples from our ongoing research project; Skåne food innovation system with a gender perspective. It has become clear that gender awareness might be a key for innovative renewal of the food industry; for promotion of the development of the food industry cluster further and at the same time strengthening regional development by acknowledge women's entrepreneurship.
Keywords: 330; Gender equality; innovation; food industry; regional development; learning